Flagship 6: Cross-cutting gender research and coordination - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2018)
Gender dimensions of agricultural growth and rural transformation ● Women’s empowerment: measurement, why it matters, and how to foster it ● Gender equality in decision making, control of assets, and benefits ● CGIAR collaborative platform for gender research